UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA DALAM MATA PELAJARAN SOSIOLOGI DENGAN MODEL JIGSAW KELAS X. 5 DI SMAN 10 PEKANBARU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
The fact that is found sometimes still far from expectations, such as those foundin SMAN 10 Pekanbaru, there are many teachers who teach sociology using the lecture method,as I observed, it turns out the lecture method is less attractive and less arouse studentsâ interestand activity. One method that can be used to increase student activity is a discussion group.Seeing realities encountered in the classroom, then I found the student activity in SMAN 10Pekanbaru in Sociology learning is still lacking. Desired activity is activity as expressed by PaulD.Dierich in Oemar Hamalik (2001: 173), which suggests that this type of activity in oral or oralactivity is put forward a fact or principle, linking an event, ask questions, give advice, expressopinions , interviews, and discussions.For it is necessary to change the model of learning to the learning objectives can be achievedand the attitudes and interests of students also changed as indicated by increasing student learningactivities with creative thinking in the learning process. Seeing the studentsâ abilities andcircumstances of the class, so I tried to use a learning model with jigsaw cooperative learningmodel.In the discussion section can disimpulkann that studentsâ motivation through the use ofcooperative learning model increased to 77.57%, while answering and responding to be 95.68%.Indicators of the presence of the third cycle changes are more interested and enthusiastic studentsto attend the lessons. It can be concluded that, participation from students who performed in thethird cycle has increased in all indicators.Keywords: Studentsâ motivation, cooperative leraning Jigsaw.